2012
DOI: 10.1089/gtmb.2011.0197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Origin of the Jordanian Population: An Analysis ofAluInsertion Polymorphisms

Abstract: Our results are compatible with ancient peoples' movements from Arabia to ancient Mesopotamia and North Africa as proposed by historians and supported by previous genetic results. The original genetic profile of the Jordanian population, very likely Arabian Semitic, has not been subject to significant change despite the succession of several civilizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Alu markers but including a wider number of populations (21) In comparison with previous data, Alu frequencies in general Jordanians are substantially similar to those previously reported for a partial sub-set of Alu markers (10 out the 18) in a Jordanian sample (Bahri et al, 2011), except for 2 (D1: p=0.02 and HS4.32: p=0.006). These few differences could be related to the potentially diverse origin of the individuals sampled in each case.…”
Section: Alu Insertion Frequencies and Gene Diversities In Bedouins Andsupporting
confidence: 86%
See 1 more Smart Citation
“…Alu markers but including a wider number of populations (21) In comparison with previous data, Alu frequencies in general Jordanians are substantially similar to those previously reported for a partial sub-set of Alu markers (10 out the 18) in a Jordanian sample (Bahri et al, 2011), except for 2 (D1: p=0.02 and HS4.32: p=0.006). These few differences could be related to the potentially diverse origin of the individuals sampled in each case.…”
Section: Alu Insertion Frequencies and Gene Diversities In Bedouins Andsupporting
confidence: 86%
“…As far as we know, previous genetic information about Jordanian populations include two studies on uniparental markers analyzed in Bedouins and General Jordanians (Flores et al, 2005;González et al, 2008) and a survey of a reduced number of Alu insertions, fewer than those analyzed in this study, in a sample of general population (Bahri et al, 2011) In this study 18 Alu insertion markers were selected because they are a useful tool for population studies on the basis of their identity by descent, known ancestral state and their selective neutrality (Cordaux et al, 2006;Cordaux & Batzer, 2009). The potential usefulness of specific Alu loci as ancestry informative markers has been explored to detect differences between populations and to estimate bio geographical ancestry (Luizon et al, 2007).…”
Section: Current Inhabitants Of Jordan Are Mostly Arab Descendants Ofmentioning
confidence: 99%
“…Accordingly, several genetic studies (e.g. Chaabani, 2002;Cerný et al, 2011;Bahri et al, 2012) have suggested ancient demographic movements from Arabia (particularly Yemen) to ancient Mesopotamia and North Africa as proposed by some historians (e.g. Goodspeed, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, both Alu and short tandem-repeat (STR) polymorphisms, used separately, have given useful information (e.g. Terreros et al, 2009;Bahri et al, 2012Bahri et al, , 2013Triki-Fendri et al, 2013). However, the combined use of haplotypic variation consisting of both a fast-evolving STR and a slow-evolving Alu marker (Alu/ STR compound system) has provided more anthropological details.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, our genetic studies (Bahri et al 2008, Ben Halima et al 2015 show a substantial degree of genetic homogeneity in the current Tunisian population. Moreover, Bahri et al 2012 showed that the two principal ethnic components, Berber and Arab, are genetically close and, therefore, have a common ancestry. This is in agreement with my suggestion that ancient human movements occurred from Arabia to ancient Mesopotamia and North Africa (Chaabani 2002;2014 Egyptian government were in a similar situation and therefore the overthrow of the latter "Egypt'coup" has surely caused a serious negative effect on the transitory Ennahdha government.…”
Section: The Cultural and Ethnic Homogeneity Of The Tunisian Populationmentioning
confidence: 99%